Observational properties of a Type Ib supernova MASTER OT J120451.50+265946.6 in NGC 4080. Issue 4 (15th March 2019) - Singh, Mridweeka; Misra, Kuntal; Sahu, D K; Dastidar, Raya; Gangopadhyay, Anjasha; Srivastav, Shubham; Anupama, G C; Bose, Subhash; Lipunov, Vladimir; Chakradhari, N K; Kumar, Brajesh; Kumar, Brijesh; et al.
ABSTRACT: MASTER OT J120451.50+265946.6 (M12045), discovered by the MASTER Global Robotic Net, is a Type Ib supernova (SN) that exploded in NGC 4080. We present the BVRI photometric and spectroscopic observations up to ∼250 d since B max . At the time of discovery the SN was a few weeks past maximum light and our observations capture the linearly declining light-curve phase. M12045 declines faster as compared to SNe 1999dn and 2009jf at comparable epochs. Rigorous spectroscopic monitoring reveals that M12045 is a normal Type Ib SN. The analysis of the nebular phase spectra indicates that ∼0.90 M⊙ of O is ejected in the explosion. The line ratio of [O i ] and [Ca ii ] in the nebular phase supports a massive WR progenitor with main-sequence mass of ∼20 M⊙ .